Factors Affecting the Research Productivity of Lecturers at the Muhammadiyah Selong Institute of Social and Health Technology - Yuniarti, Ratna; Bahri, Salmi Yuniar; Affandy, Yuniar (International Journal of Applied Research and Sustainable Sciences, 2024)
This research is a qualitative analysis of lecturers' research productivity. This productivity is viewed from law about teachers and lecturers and Republic of Indonesia Government Regulations about lecturers. Especially the research areas in the rubric (PO BKD)which is monograph or reference book, producing work published in international journals and national journals. Meanwhile, the factors that influence productivity observed are Institutional Support, Digital Literacy, Rewards, Sanctions, and Competence. The subjects in this research were 14 ITSKes Muhammadiyah Selong lecturers from all study programs. Data collection was carried out by interviews and distributing perception questionnaires. The results of this research show that the productivity level of lecturers who have high academic positions are more productive in support. Then institutions and digital literacy skills have a big influence on lecturer productivity, while rewards and sanctions are quite influential.